Educação para quem? Um estudo dos programas E-Futuro e Protege - Pereira, Alessandra Rodeiro (2019)
In the 2000s the use of technology in schools was a highlight in international and national events. In Brazil there has been and still is a consensus among educators on the integration of information and communication technologies in education and, because of all this appeal, Brazil adheres to the Globally Structured Agenda for Education, which aligns Education with the socio-economic context. economic and technological. The work presented sought reading in the critical sociological, based on the ideas of Bourdieu and Dale, the programs E-Futuro and PROTEGE, the municipal network of Aracaju, from a historical research, having as empirical field the Municipal School of Elementary School Tenisson Ribeiro, in order to identify motivations, methodologies, implementation and follow-up process, results obtained, impacts, resistances and continuity of these programs. It brings a qualitative approach, working with the techniques of archiving and semi-structured interviews, with the intention of understanding and interpreting the phenomena. Educational issues are presented, as well as the economic and political scenario of Brazil and Aracaju, from 2012 to 2016, in which such programs were implemented. In the end it was found that the programs were implemented without considering the real needs of the network, without the necessary adaptations and without the necessary financial impact study and action planning; highlighting the lack of commitment in the use of public resources and confirming the logic that education was not the priority of public management in both periods; neither the local interests of the school nor the interests of the global agenda were the focus of the programs; What was seen was the global agenda being used as a justification for the pursuit of particular interests of groups that take turns in power.